Chimonanthus nitens Oliv. Leaf Granule Ameliorates DSS-Induced Acute Colitis Through Treg Cell Improvement, Oxidative Stress Reduction, and Gut Microflora Modulation - Huang, Jia-Qi; Wei, Si-Yi; Cheng, Nian; Zhong, You-Bao; Yu, Fei-Hao; Li, Ming-Da; Liu, Duan-Yong; Li, Shan-Shan; Zhao, Hai-Mei (Frontiers in Cellular and Infection Microbiology, 2022)
The rising incidence of ulcerative colitis has become a new challenge for public health. Chimonanthus nitens Oliv. Leaf Granule (COG) is a natural medicine used for the treatment of respiratory diseases which have excellent anti-inflammatory and anti-oxidant effects. However, the therapeutic effect of the COG in UC has not been reported. Here, the experimental colitis was treated by dextran sodium sulfate (DSS), and COG treatment. After treatment with high (30 g/kg), medium (15 g/kg) and low (7.5 g/kg) doses COG for consecutive 11 days, the body weight, disease activity index (DAI) score, colon length, colon weight index, and pathological score of mice were effectively improved. COG significantly reduced the levels of inflammatory cytokines on UC mice in vitro and in vivo, and restored the secretion levels of IL-6 and IL-10 in colon. Meanwhile, compared to mice with colitis, COG-treated mice showed lower levels of MDA, MPO, NO and e-NOS, and higher levels of GSH-Px and MAO, which indicated that oxidative stress damage of colitis mice was alleviated by COG. Moreover, less Th17, more Treg were observed in COG-treated groups. Not only that, COG improved the diversity and relative abundance of gut microflora in colon of colitis mice, Lachnospiraceae_NK4A136_group and Lachnospiraceae_UCG-006 were obviously regulated on genus level. In summary, COG has a protective effect on DSS-induced experimental colitis, mainly through the inhibition of immune inflammatory responses, oxidative stress and regulation of mTreg cell responses and intestinal flora composition.